Computer Highlights Society Magazines. (Computer (00189162), 2009)
Articles published in journals printed by the IEEE Computer Society are noted. Features in the November/December, 2008 "IEEE Software" on dealing with communication issues in software project management are characterized. A piece in the November/December, 2008 issue of "IT Professional" on professionalism in information technology is presented. An article on the history of the computer company SAP AG in the October-December, 2008 "IEEE Annals of the History of Computing" is also presented.